Uma investigação histórica sobre o bispado de Dom Jaime Collins no antigo norte goiano (1960 – 1999) - Ribeiro, Luciene de Sousa (2022)
This dissertation is the result of a qualitative research that was developed within the scope of the Post-Graduate Program in History of the Amazonian Populations and its general objective is to investigate and document the trajectory of Bishop James Collins, C.Ss.R., in the period from 1960 to 1999. He was an Irish Redemptorist missionary who lived this period in Brazil, mostly as bishop of the Diocese of Miracema, currently belonging to the State of Tocantins. Initially we sought to understand the motivation of the coming of missionary James Collins as Superior of a mission to Brazil and from 1966, how he worked as bishop of the Prelature of Miracema, especially in that critical period of Brazilian history, the military dictatorship. The sources of research are documentary, found in the archives of the places where the bishop lived; oral, through interviews with 7 people, who were part of the bishop's trajectory and who agreed to contribute with their memories; and articles available in newspapers of the time. The study is anchored in the methodological theoretical framework of the following scholars: 1) Certeau (1982) and Veyne (1998), with regard to the procedure of historiographical research and about the writing of history; 2) Burke (1991) and Le Goff (1990), to understand research from the perspective of "new history"; 3) Pollak (1989) and Meneses (1992), with their studies on history and memory and; 4) Portelli (2016) and Meihy (1996) on oral history, among others. The results indicate that the coming of this mission of the Irish Redemptorists to Brazil had as a backdrop a request from Don Alano do Noday and the performance of Don Jaime was based on the teachings of the Second Vatican Council (1962– 1965), which sought a church that was closer to the people, more human. This led Bishop Collins to pursue public policies, especially in the areas of education and health, as well as supporting small farmers and the struggles of squatters in search of agrarian reform. He also supported the unions and associations, in an unsuccessful attempt to insert articles into the Constitution of the new state (of Tocantins). In the course of the research, the sources led to an understanding of the Church's perspective with regard to the performance of religious sisters (nuns) in the post-Second Vatican Council, given that they were at the forefront of activities commonly considered to be the realm of the clergy. Although it did not mean a structural change in the hierarchy of the Catholic Church, Bishop Collins was able to count on their valuable contribution in the period. At any rate, it can be said that Bishop James Collins was an historical man, a product of his time. Despite having his memories outside the Catholic Church unknown, his actions, as well as those of the entire Irish Redemptorist mission, are alive in the memories of the people who lived with the bishop here in Brazil. This research denotes a contribution to future work, and so does not exhaust the possibilities of more research on this mission to Brazil. On the contrary, we hope that it will be able to prompt further studies so that new histories can be investigated.